Penggunaan Media Video Animasi dalam Pembelajaran Keterampilan Menulis Cerita di Madrasah Ibtidaiyah Nurul Islam Lumajang - Muhammad Abdul Halim Sidiq; Siti Rosidah; Moch. Shohib (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2021)
The low learning quality and results can be caused by a lack of interest and attention of students to subjects. As an alternative solutions, effective and attractive learning media are needed, such as the learning media used by teachers in Mi Nurul Islam Selok Awar-Awar, Lumajang, East Java. That is an animated video to improve story-writing skills. This article is prepared with a qualitative approach and a field research type. This article examines the use of animated videos classified as audio-visual media in thematic learning of writing skills in Mi Nurul Islam Selok Awar-Awar, Lumajang Regency. In its implementation, the teacher applied four stages: the stage of learning preparation, the opening stage of learning, the core stage of learning and the learning closing stage.Rendahnya kualitas dan hasil pembelajaran, dapat disebabkan oleh faktor kurangnya minat dan perhatian peserta didik terhadap mata pelajaran. Alternatif solusinya, dibutuhkan media pembelajaran yang efektif dan atraktif, seperti media pembelajaran yang digunakan oleh guru di MI Nurul Islam Selok Awar-Awar, Lumajang, Jawa Timur. Yaitu video animasi untuk meningkatkan keterampilan menulis cerita. Artikel ini disusun dengan pendekatan kualitatif dan jenis penelitian lapangan. Artikel ini menelaah penggunaan video animasi yang tergolong media audio-visual dalam pembelajaran tematik keterampilan menulis cerita di MI Nurul Islam Selok Awar-Awar, Kabupaten Lumajang. Dalam implementasinya, guru menerapkan empat tahap: Tahap Persiapan Pembelajaran, Tahap Pembuka Pembelajaran, Tahap Inti Pembelajaran dan Tahap Penutup Pembelajaran.